ETHNIC PREJUDICE AND THE PROBLEM OF PEACEFUL CO-EXISTENCE IN NIGERIA - Agbakwuru, Chikwe; Opara, M. I. (European Scientific Journal, ESJ, 2013)
This paper investigated ethnic prejudice and its challenges to peaceful co-existence in Nigeria. The study was carried out with 300 N.Y.S.C. members who were drawn through purposive sampling technique from their orientation camp in Imo State. Relevant data for answering the five research questions posed for the study were collected from the respondents through personal contact method of administration of copies of structured, researchers’ – developed questionnaire called Ethnic Prejudice Questionnaire. The reliability of this instrument was carried out through a test-retest method with 20 subjects within an interval of two weeks. The obtained reliability co-efficient was 0.81. The research questions were answered with percentage and the results among other things show that ethnic prejudice still poses a challenge to peaceful co-existence in Nigeria. The results were discussed and some counselling implications were also stated. One of these is that counsellors should employ the emotive – evocative technique in helping clients to understand the differences between their prejudices and the truth.